DATA and Information in Architectural Design Process Through Building Information Modeling (2020)
This paper takes up the results of two research projects led by the authors: Contemporary Architecture in Colombia and Optimization of building management through the implementation of digital twins. These results are applied to a pedagogical investigation on the work developed in an architectural design workshop. The experience of the Architecture and BIM workshop of the Universidad de Bogotá Jorge Tadeo Lozano (UTADEO) is presented. This academic space, which responds to some challenges of the implementation of the BIM building information modeling in university education in Colombia, uses BIM methodology to train the student in architectural design competencies. It highlights the one corresponding to the integration of the technical dimension and its impact on space design decisions. The experimental exercise in the workshop seeks to transpose the methodological and technological advances derived from the digital transformation of the industrial sector to the training processes in the academy. This strategy links the information modeling of the building as a method to generate a change of the projective thinking and to improve the decision-making for the production of architecture. In the second part of the article, on section four, from the results of the workshop experience, we proceed to discuss the digital interface where data and information collide and the architecture teaching model in Colombia and to outline a new, more appropriate and current epistemological point of view for architecture education. This exploration of the ‘data’ theme in architecture design process through both a practice-based and a theoretical approach suggests a prospect for the future professional practice and its associated training processes. The possible widespread implementation of these new ways of projecting can lead to the development of a new epistemological model for architecture education in Colombia, in accordance with disruptive practices such as the design process under the influence of digital transformation.